2022
DOI: 10.3390/foods11213528
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Preparation and Action Mechanism of Natural Deep Eutectic Solvents and Their Application in Food

Abstract: Natural deep eutectic solvent (NADES) is the eutectic mixture which is formed by hydrogen bond donors (HBDs) and hydrogen bond acceptors (HBAs) with a certain molar ratio through hydrogen bonding. NADES is a liquid with low cost, easy preparation, biodegradability, sustainability and environmental friendliness at room temperature. At present, it is widely used in food, medicine and other areas. First, the composition, preparation and properties of NADES are outlined. Second, the potential mechanism of NADES in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Various techniques can be employed to prepare DES such as heating, grinding, vacuum evaporation and freeze‐drying 23 . The choice of preparation method is typically influenced by factors like personal preference, equipment availability and the aim of reducing water content 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques can be employed to prepare DES such as heating, grinding, vacuum evaporation and freeze‐drying 23 . The choice of preparation method is typically influenced by factors like personal preference, equipment availability and the aim of reducing water content 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Various techniques can be employed to prepare DES such as heating, grinding, vacuum evaporation and freeze-drying. 23 The choice of preparation method is typically influenced by factors like personal preference, equipment availability and the aim of reducing water content. 24 Among these techniques, the heating method garners the most attention in scholarly works due to its simplicity, minimal equipment requirements and effectiveness in minimising water content in the developed DESs, which is particularly important considering the hygroscopic properties of their constituents.…”
Section: Preparation Of Dessmentioning
confidence: 99%
“…Overall, these diverse synthesis techniques contribute to the preparation and development of NADES. More information about these preparation methods can be find in recent reviews (Mišan et al 2020 ; El Achkar et al 2021 ; Omar and Sadeghi 2022 ; Wu et al 2022 ).
Fig.
…”
Section: Nadess Preparationmentioning
confidence: 99%
“…
Fig. 1 Different methods for the preparation of natural deep eutectic solvents from malic acid and choline chloride, with the permission of Wu et al ( 2022 )
…”
Section: Nadess Preparationmentioning
confidence: 99%
“…The higher value of the Ca 2+ -ATPase activity of the NADES group sample compared to that of the SS group sample indicated that the NADES was more effective in inhibiting the decrease in the Ca 2+ -ATPase activity. This is attributed to the fact that the hydrogen bonding network system of NADES effectively inhibits water movement and reduces the generation of ice crystals, reducing the mechanical damage of ice crystals to muscle tissues [36], thus inhibiting conformational changes and the denaturation of myosin head and consequently stabilizing the Ca 2+ -ATPase activity.…”
Section: Inhibition Of Nades On Ca 2+ -Atpase Activity Of Frozen-thaw...mentioning
confidence: 99%